Pharmacological treatment for pubertal progression in boys with delayed or slow progression of puberty: A small-scale randomized study with testosterone enanthate and testosterone undecanoate treatment - Österbrand, Martin; Fors, Hans; Norjavaara, Ensio (Frontiers in Endocrinology, 2023)
Context The use of testosterone enanthate (TE), 50–75 mg intramuscularly (i.m.)/month, for the treatment of boys with delayed puberty or slow progression to induce puberty is the standard of care (SoC) in Sweden. This treatment is empirical and has not been scientifically evaluated. Replacement therapy in hypogonadal boys/young men in Sweden after induction is mainly performed with testosterone undecanoate (TU), 1,000 mg/3 months. TE is only available on license. TE was deregistered in Sweden in 2006. Therefore, this study was initiated to compare the two products. Objective To clinically evaluate pubertal progression with six injections of TE, 75 mg i.m./month (1/3–1/5 of adult dose), compared with two injections of TU, 250 mg i.m./3 months (1/4 of adult dose). Trial design In the Pubertal Replacement in Boys Study (PRIBS), boys aged 14–16 years in West Sweden with pubertal delay were randomized in a parallel study to TE or TU for pubertal progression. Inclusion criteria were morning testosterone levels of 0.5–3 nmol/L and testicular volume ≤6 ml. Between June 2014 and Nov 2019, 27 boys were included. Methods The primary outcome was testicular enlargement ≥8 ml after 12 months. TU treatment was considered clinically similar if the number of boys with testicular enlargement ≥8 ml was 80%–125% of the number of boys with TE. Fisher’s exact chi-square test was used for this analysis. Results Both treatments were well tolerated. Twelve of 14 (86%) TU-treated boys reached the primary outcome and 12/12 in the TE group. Fisher’s exact chi-square testing indicated a one-sided p-value of 0.28 (the two-sided p-value was 0.483). The TU treatment was considered not clinically different from SoC. A post-hoc study showed 25% power. Therefore, no evidence-based conclusion can be drawn from the results even if the clinical data support a similar effect of the treatments. Conclusion The present small-scale study supports that both TE and TU had similar effects in terms of pubertal progression. Clinical Trial Registration https://www.clinicaltrials.gov/ct2/home, identifier NCT05417035; https://www.clinicaltrialsregister.eu/ctrsearch/search, identifier EUDRACTEudraCT nr 2012-002337-11.